Nurses’ perception on mental health interventions in Primary Health Care - Rafaela Sales Medeiros; Divane de Vargas; Jaqueline Lemos de Oliveira (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objectives: to verify the perception of Primary Health Care nurses regarding mental health interventions used in their daily work. Methods: quantitative, descriptive-exploratory study, developed in 66 Primary Health Care Units. The sample consisted of 239 nurses. For the descriptive analysis, according to the interventions recommended in the national guidelines and systematic reviews, the practices were classified into three components: universal practice (I), specifically in mental health (II) and educational and universal practices (III). Results: regarding component I, most participants considered all items as being within their attribution and possible to perform, only for the item Integrative and Complementary Practices, most participants did not consider themselves qualified. Among the specific mental health activities, the items therapeutic interpersonal relationships, advanced practices in rehabilitation, therapeutic groups and application of scales were those for which nurses considered themselves least qualified to perform. Regarding component III, continuing education, this was the item for which only 40% of nurses considered themselves qualified to perform. Conclusions: it was found that nurses recognize mental health practices in their daily service, as well as perform them and understand them as being within the scope of their actions; however, there is still the perception that they do not feel qualified to perform such practices.